Assess the Impact of Uganda`s Oil and Gas Industry on the Ecosystem Services and Living Conditions of Small Farmers in the Albertine Region - Hope Iremera (Uganda Christian University, 2025)
The study examined the impact of oil and gas industry on the ecosystem services and living conditions of small farmers in the Albertine region. The unclear connection between exploration, resource extraction, and the resulting negative social impacts has sparked much debate in Africa. Consequently, numerous scientific papers have attempted to clarify this relationship from various perspectives, including the original theory of flight and several evolutionary and dependency theories. It was guided by the following objectives to examine the impact of oil and gas industry on agricultural ecosystems, to examine the extent of environmental degradation resulting from oil and gas activities, to analyze the effectiveness of existing environmental protection policies and mitigation strategies. The study adopted Modernization theory explains the process of modernization of society. The theory of modernization is based on the ideas of the German sociologist Max Weber (1864-1920). The study employed both qualitative (interview) and quantitative (survey) research methods were utilized. This was aided with a sample size of 184 is sufficient. The study reveals a moderate level of awareness and confidence in the implementation of environmental protection policies among communities affected by oil and gas activities in Uganda, with an overall mean of 3.20 (SD = 1.08). Respondents generally believe that environmental laws are enforced (mean = 3.81) and that oil companies follow government guidelines (mean = 3.66). The government, through agencies like the National Environment Management Authority (NEMA) and the Petroleum Authority of Uganda (PAU), should strengthen enforcement of environmental regulations, particularly around land use, water protection, and biodiversity conservation.
Undergraduate research